Effects of the human-mobility change during the COVID-19 pandemic on electricity demand - Kentaka Aruga (Journal of Risk and Financial Management, 2022)
This study investigated how the changes in the number of people's visits to various locations during the COVID-19 pandemic influenced electricity demand. Using the autoregressive distributed lag (ARDL) model, the study reveals that while an increase in visits to groceries, pharmacies stores, and transit stations increased electricity demand, an increase in the hours people spent at home had a negative impact on the demand during the period of the state of emergency (SOE). This study also demonstrates the differences in the effects of human-mobility changes on electricity demand among different SOE periods, which was probably related to the weakening in the effect of the SOE measures as people became accustomed to the SOE announcements. As the energy transition unfolds across the world, ensuring the optimization of integrated energy systems has never been more important; thus, the current study suggests that controlling human mobility could be one of the options through which policymakers could intervene in the energy-demand sector.
Keywords: 650; COVID-19; human mobility; electricity demand